Efektivitas Isolat Bakteri dari Rizosfer dan Bahan Organik Terhadap Ralstonia solanacearum dan Fusarium oxysporum pada Tanaman Kentang - Tutik Kuswinanti; Baharuddin Baharuddin; Sri Sukmawati (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2014)
Rhizosphere is an ideal area for growth and development of microbial antagonists, because it is a nutrition rich area. Nutrients that secreted in the rhizosphere are influenced by many environmental factors which in turn effect the diversity and abundance of microbial community. Based on these facts, the research were aimed to isolate bacteria from the rhizosphere and organic materials in Tana Toraja, and determine their role as biological control agents for potato wilt disease. Antagonistic test was conducted in order to determine the ability of each bacterial isolate to inhibit the growth of Ralstonia solanacearum and Fusarium oxysporum. The results showed that from totally 74 bacterial isolates, only 10 and 4 bacterial isolates were able to inhibit the growth of R. solanacearum and F. oxysporum in vitro, respectively.